Independency of Investigators in Conducting Investigations in Cases of the Crime of Premeditated Murder Pasal 340 KUHP - Juel Salem Gea Jimi; Dahris Siregar; Anugerah Gea Berkat; Kasih Gulo; Alif Muhammad Ofar Sembiring San; Putra Harapan Gulo Windri Gea; Jetisman Hulu Agus; Ria Mendrofa (Jurnal Smart Hukum (JSH), 2023)
Investigation is the first step in disclosing a criminal case before entering the investigation stage. The importance of investigations carried out by investigators is to obtain detailed information on the field or crime scene both in the form of statements from eyewitnesses and the results of investigators' investigations. In carrying out an investigation, it is hoped that the independence of the police as investigators, especially if the crimes that occur are complex in nature, such as the crime of premeditated murder. However, in carrying out investigations, investigators often experience various obstacles and intervention from outsiders who feel they have an interest in the case being investigated is no exception, so it takes quite a long time. In this study the authors used a normative juridical research method, namely an approach method based on a study of existing laws and applicable laws and regulations. This study aims to determine the importance of the independence of the police as investigators and the legal basis governing independence itself, in order to create a sense of justice in disclosing a case of premeditated murder starting from the earliest stages.